2016
DOI: 10.1128/aem.02092-15
|View full text |Cite
|
Sign up to set email alerts
|

Using UVC Light-Emitting Diodes at Wavelengths of 266 to 279 Nanometers To Inactivate Foodborne Pathogens and Pasteurize Sliced Cheese

Abstract: UVC light is a widely used sterilization technology. However, UV lamps have several limitations, including low activity at refrigeration temperatures, a long warm-up time, and risk of mercury exposure. UV-type lamps only emit light at 254 nm, so as an alternative, UV light-emitting diodes (UV-LEDs) which can produce the desired wavelengths have been developed. In this study, we validated the inactivation efficacy of UV-LEDs by wavelength and compared the results to those of conventional UV lamps. Selective med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 18 publications
3
63
0
3
Order By: Relevance
“…It has been shown that UV sensitivity differs among different groups of micro-organisms, and that gram-negative bacteria are generally more sensitive than gram-positive bacteria, yeast, bacteria spores, molds, or viruses [40,41]. Similarly, our study showed that localized UV-C lamps were more effective for eliminating E. colifrom airborne bioaerosols than for eliminating S. Epidermidis or S. typhimurium.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It has been shown that UV sensitivity differs among different groups of micro-organisms, and that gram-negative bacteria are generally more sensitive than gram-positive bacteria, yeast, bacteria spores, molds, or viruses [40,41]. Similarly, our study showed that localized UV-C lamps were more effective for eliminating E. colifrom airborne bioaerosols than for eliminating S. Epidermidis or S. typhimurium.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, our study showed that localized UV-C lamps were more effective for eliminating E. colifrom airborne bioaerosols than for eliminating S. Epidermidis or S. typhimurium. Salmonella species were found more resistant to UV-C than E. coli [40].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The current finding agrees with the previous discussion of the log‐reductions in CFU counts, which showed that the gram‐positive bacterium, S. epidermidis , due to its thicker cell wall was less susceptible to irradiation by both the UR‐UVGI‐LED and the conventional UR‐UVGI‐MV systems than the gram‐negative bacteria, E. coli, and S. marcescens . Previous studies have suggested that S. epidermidis has similar responses to UV irradiation …”
Section: Resultssupporting
confidence: 92%
“…Shin et al reported that UVC LED intensity was not influenced by temperature change and no warm-up time was required for maximum intensity output, whereas LP lamps had decreased output intensity at low temperature and a warm-up time of about 5 min was required (21). In addition, UVC LEDs showed much higher inactivating efficacy against Escherichia coli O157:H7, Salmonella enterica serovar Typhimurium, and Listeria monocytogenes than LP lamps at the same dosages with intensity adjustment (22). MS2, Q␤, and X174, human enteric virus surrogates, effectively lost their infectivity in batch and continuous-type water disinfection systems incorporating UVC LED arrays (23).…”
mentioning
confidence: 99%